EAP1216 “The Djerba Libraries Project:” A New Manuscript Digitization Project in Djerba, Tunisia | مكتبات جربة: مشروع جديد لرقمنة المكتبات بجربة (تونس) - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2019)
I am delighted to announce the launch of “EAP1216 The Djerba Libraries Project,” a two-year effort to digitize several libraries on the island of Djerba, Tunisia. Funded by Arcadia (a c…
Keywords: Manuscrits – Conservation; Manuscrits – Djerba

Preserving Endangered Archives in Jerba, Tunisia: The al-Bāsī Family Library | الحفاظ على الأرشيفات المهدّدة في جربة: مكتبة الباسي العائلية - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2018)
The Journal of Manuscript Studies (3:1, Spring 2018) has just published a short research annotation by my colleague Dr. Ali Boujdidi and myself, describing our project on the El Bessi (al-Bāsī) fam…
Keywords: Manuscrits – Conservation; Manuscrits – Djerba

Announcing a new manuscript conservation effort in Djerba, Tunisia: the El Bessi Library Project | إعلان بمشروع جديد للحفظ على المخطوطات في جزيرة جربة: مشروع مكتبة جامع الباسي - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2017)
Keywords: Bibliothèques – Djerba; Manuscrits – Conservation; Manuscrits – Djerba

جهود حماية مخطوطات وادي مزاب وقراءة وصفية لفهارسها - باباواسماعيل, زهير بن مسعود (مجلة التراث, 2012)
Keywords: Manuscrits – Conservation; Manuscrits – Mzab

جليل التعامل مع المخطوط = Guide de la manipulation du manuscrit - قزريط, داود بن موسى; دادي بابا, عمر (جمعية الشيخ أبي إسحاق إبراهيم اطفيش لخدمة التراث, 2017)
Keywords: Manuscrits – Conservation; Manuscrits – Mzab

مشاريع الرقمنة ودورها في تثمين وإتاحة المخطوطات: جمعية الشيخ أبي إسحاق إبراهيم اطفيش لخدمة التراث بولاية غرداية نموذجا - دادي نونو, رستم; قزريط, داود بن موسى (جامعة قسنطينة 2, 2016)
Keywords: Manuscrits – Conservation; Manuscrits – Mzab

Waraqa ḥawla Tajribat Jamʿiyyat al-Shaykh Abī Isḥāq fī Ta’mīn al-Makhṭūṭ ḍimna Barnāmaj ONG II - Syūsyū, Ṣāliḥ b. Bakīr (Al-Minhāj, 2011)
Keywords: Manuscrits – Conservation; Manuscrits – Mzab

حماية خزائن المخطوطات في وادي مزاب بغرداية وفهرستها - باباواسماعيل, زهير بن مسعود (الذاكرة, 2014)
Keywords: Manuscrits – Conservation; Manuscrits – Mzab